GREEN CORROSION INHIBITOR FOR METAL IONSIN ACIDIC MEDIUM DATURA STRAMONIUM EXTRCT - Dr.Kailash Chand (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
This study investigates the efficacy of Datura stramonium extract as a green corrosion inhibitor for metal ions in acidic medium. The focus is on evaluating the extract's ability to mitigate corrosion of metal surfaces exposed to acidic environments, which are commonly encountered in industrial processes. The corrosion inhibition potential of Datura stramonium extract was assessed through various techniques, including weight loss measurements, electrochemical impedance spectroscopy (EIS), and potentiodynamic polarization studies. Results indicate that the extract exhibits significant inhibition efficiency, attributed to the presence of phytochemicals that adsorb onto the metal surface, forming a protective layer. This eco-friendly inhibitor offers a sustainable alternative to traditional, more hazardous corrosion inhibitors. The findings underscore the potential of Datura stramonium extract in extending the lifespan of metal equipment and structures, thereby reducing maintenance costs and environmental impact.